Analisis Pola dan Perilaku Konsumsi Beras oleh Rumahtangga Peserta Program Keluarga Harapan di Kota Pekanbaru - Zahry Aditya; Syaiful Hadi (Universitas Galuh, 2026)
Rice consumption in Pekanbaru City fluctuated during the 2020–2024 period, with an increase in 2021 and a decrease in 2022. Rice prices have also fluctuated over the past five years, while per capita rice expenditure has continued to increase, particularly among poor households who allocate a larger portion of their expenditure to food. This study aims to describe rice consumption patterns based on household size, the education level of the mother or head of the household, and the type of employment; analyze the dominant factors influencing rice consumption among PKH recipient households; and analyze the responses of the dominant factors influencing rice consumption. This study used primary and secondary data with a multistage sampling method. The total sample consisted of 315 households. The results showed that rice consumption among PKH participant households exceeded daily carbohydrate requirements. Households with a larger number of family members tended to have higher total rice consumption. Based on education level, households with secondary education consumed more rice than those with primary or higher education. Meanwhile, based on occupation, households with jobs in the informal sector had slightly higher rice consumption than those in the formal sector. The dominant factors influencing consumption include the price of rice, the price of instant noodles, the price of tubers, the number of household members, income, and occupation.